Analysis of the Increase in Exports and Imports and Their Effect On the Trade Balance in Indonesia In 2017-2021 - Abdul Latif; Andi Mardiana; Husni Nurul Hikmah Yusuf (Gorontalo Development Review, 2022)
The goal of this study was to ascertain whether exports and imports had a positive or negative impact on a country's trade balance. The secondary data used in this analysis pertains to the total value of non-oil and gas-oil and gas imports and exports as well as the trade balance for the years 2017 through 2021. The Central Bureau of Statistics for 2017–2021 as well as the Ministry of Trade of the Republic of Indonesia's official websites were studied and analyzed by the researcher as part of the data collecting procedure using library research methodologies. According to the study's findings, the trade balance declined by 65% in 2019; there was a deficit of 3,044.4 million US dollars, which is a difference of 5,654.1 million US dollars from the previous year. However, the overall value of exports increased by 41.9% in 2021 compared to 2020, generating a surplus in the trade balance of 35,332.5, up 63.4% from the value of the trade balance prior year.